INVESTIGATING THE FACTORS ASSOCIATED WITH MENTAL WELLBEING OF POST GRADUATE NURSING STUDENT IN UNIVERSITY OF SUNDERLAND, UNITED KINGDOM - Okeizu, Ogechukwu; Silas, Esther A; Snow, Dawn (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
The aim of this research work was to investigate the factors that are associated with the mental wellbeing of post graduate students in the university of Sunderland, United Kingdom. The study utilized a quantitative survey with a positivist epistemology approach in its investigative process. A convenience sampling technique that included all the post graduate nursing students at the university (98 students) was employed. The online survey link that contained the structured questions was distributed to participants by the gate keeper. Data were statistically analyzed using SPSS software. A significant association was found between good general wellbeing and religion (X2 = 9.291, p = 0.026), Student status (X2 = 4.409, p = 0.036) and marital status (X2 = 8.712, p = 0.033). More so, significant associations were identified between good academic wellbeing and the respondent’s gender, ethnicity, age, student status, marital status, religion, and previous mental illness (p < 0.05). The social and environmental wellbeing of the students had a positive relationship with the participant’s religion (X2 = 36.588, p < 0.001). Several factors showed positive correlation with the mental wellbeing pf postgraduate nursing students.